Pengaruh Motivasi Belajar Dan Disiplin Belajar Siswa Terhadap Prestasi Belajar Di SMTK Waikabubak Sumba Barat - Agustinus Rina Lagu; Umar Ali; Andrian Wira Syaputra; Yakobus Adi Saingo (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study aims to determine the effect of learning motivation and student learning discipline on learning achievement at Waikabubak High School, West Sumba. This study used a quantitative method by collecting data obtained from filling out the Likert scale by 55 students. The findings and results of the study show that: there is an influence of learning motivation on student learning achievement at the Waikabubak Sumba West Vocational High School by means of a statistical test of the scores obtained Fhit = 71,752 with a significance of 0.000. As well as the contribution of learning motivation variables to learning achievement of 56.7% while the remaining (residue) 43.3% contributed by other variables not examined in this study. There is an influence of learning discipline on student achievement at Waikabubak Vocational High School students with statistical tests to obtain scores Fhit = 100,403 with a significance of 0,000.  And the contribution of the learning discipline variable to learning achievement is 65.5% while the remaining 34.5% is contributed by other variables not examined in this study. And there is an influence of learning motivation and learning discipline on student achievement at Waikabubak West Sumba High School with statistical tests to obtain scores Fhit = 70,644 with a significance of 0,000. The contribution of learning motivation and learning discipline to learning achievement is 73.1% while the remaining 26.9% is contributed by other variables not examined in this study. So it can be said that the higher the learning motivation of students and have a good level of learning discipline, the learning achievement also increases.